2021
DOI: 10.3390/nu13030867
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Intake of Endocrine Disrupting Substances Presents in Environment and Their Impact on Thyroid Function

Abstract: According to the available data, environmental pollution is a serious problem all over the world. Between 2015 and 2016, pollution was responsible for approximately nine million deaths worldwide. They also include endocrine disrupting chemicals (EDCs) that can interfere with the functioning of the thyroid gland. They are characterized by high persistence in the environment. These substances can enter the body through the gastrointestinal tract, respiratory system, as well as contact with the skin and overcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 146 publications
0
10
0
Order By: Relevance
“…EDCs affect thyroid function in several ways, including hormone biosynthesis, transport, metabolism, and TR activity [ 97 ]. Thus, clinical and animal studies have suggested that EDC exposure could impair thyroid signaling during development and be associated with neurological deficits [ 98 , 99 , 100 ]. Clinical studies have proven that exposure to polybrominated diphenyl ethers (PBDEs) is associated with hypothyroidism [ 101 ].…”
Section: Disease Endpoints In Relation To Edcsmentioning
confidence: 99%
“…EDCs affect thyroid function in several ways, including hormone biosynthesis, transport, metabolism, and TR activity [ 97 ]. Thus, clinical and animal studies have suggested that EDC exposure could impair thyroid signaling during development and be associated with neurological deficits [ 98 , 99 , 100 ]. Clinical studies have proven that exposure to polybrominated diphenyl ethers (PBDEs) is associated with hypothyroidism [ 101 ].…”
Section: Disease Endpoints In Relation To Edcsmentioning
confidence: 99%
“…Environment (air, water and food) polluted by artificial nonorganic Cl-contained compounds, for example such as sodium chlorate (NaClO 3 ), and organic Cl-contained compounds, for example such as polychlorinated biphenyls (PCBs) and dioxin, is other source. There is a clear association between using chlorinated drinking water, levels NaClO3, PCBs and dioxin in environment and thyroid disorders, including cancer [55][56][57][58][59].…”
Section: Chlorine and Sodiummentioning
confidence: 99%
“…Phthalates, acting as plasticizers, are extensively used in daily consumer and industrial products. They have been frequently detected in both surroundings and human beings worldwide . Phthalates easily enter the body via respiratory inhalation, everyday diet intake, and epidermal absorption.…”
Section: Introductionmentioning
confidence: 99%